Retrospective analysis of cardiovascular diseases related to chemotherapies for advanced solid tumor patients. Issue 9 (October 2016) - Shirakawa, Tsuyoshi; Nakano, Michitaka; Nio, Kenta; Tamura, Shingo; Komoda, Masato; Kumagai, Hozumi; Uchino, Keita; Odashiro, Keita; Arita, Shuji; Shibata, Yoshihiro; Ariyama, Hiroshi; Kusaba, Hitoshi; et al.
Abstract : Appropriate management of cardiovascular diseases (CVDs) related to chemotherapy for solid tumors is important for safe oncologic treatment. However, prediction of the onset and progression of CVDs has not generally been established in Japan. We carried out a retrospective analysis of advanced or recurrent solid tumor patients who received chemotherapies in a single institution. Patient characteristics, chemotherapy regimens, adverse events, CVDs before chemotherapy, and diagnosis of CVDs in association with chemotherapy were assessed. During the period from April 2006 to March 2012, 394 patients were examined. Cardiac diseases (CDs), hypertension (HT), or arterial thrombosis or venous thromboembolism were prevalent in 37 (9.4%), 22 (5.6%), five (1.3%), and 14 (3.5%) cases, respectively. HT (14.5%) and venous thrombosis (5.8%) were frequent in patients who received bevacizumab-containing chemotherapy. Four cases with left ventricular dysfunction experienced a decrease of ejection fraction and early filling/atrial filling ( E / A ) and E / A tended to decrease before ejection fraction. Ninety (62.1%) of 145 cases showed an increase in the D-dimer (DD) level before chemotherapy, and a further increase in DD level was found when venous thrombosis occurred. Relative risks of the disease progression of HT, CD, and thromboembolism because of chemotherapy were 1.3, 1.9, and 3.6, respectively. A decrease in E / A and an increase in DD were suggested to be valuable for early diagnosis of the respective onsets of left ventricular dysfunction and venous thrombosis related to chemotherapy. We conclude that patients with previous CD tend to have disease progression of CD during chemotherapy.